Perbandingan Skor Objective Structured Clinical Examination (OSCE) Komprehensif Sebelum dan Saat Pandemi COVID-19 - Marita Fadhilah; Nurul Hiedayati; Erfira Erfira; Ika Alifa; Ratu Nadia Cahyaningtyas (Majalah Kedokteran Indonesia, 2023)
Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic has led to changes in the methods of teaching and assessing medical students, shifting from face-to-face to online interactions. Various modifications have been made to the Objective Structured Clinical Examination (OSCE) for achieving competency in preclinical students. However, the impact of these teaching and assessment methods during the pandemic has not been widely reported. This study aims to compare comprehensive OSCE scores before and during the COVID-19 pandemic in final-year preclinical medical students.Methods: This cross-sectional study involved data from final-year preclinical students at the Faculty of Medicine Universitas Islam Negeri Syarif Hidayatullah Jakarta (FMUINSHJ) who underwent OSCE in 2019, 2021, and 2022. The OSCE data included seven clinical competency areas. The data were then analyzed to compare the mean OSCE scores among the three student cohorts.Results: Among the three student cohorts (with respective sample sizes for 2019, 2021, and 2022: 82, 91, and 88), the highest mean score was obtained by students in the 2021 OSCE (score 63.75), while the lowest score was observed in the 2022 OSCE (score 60.20). Significant statistical differences were found among the seven competency areas in aspects such as history-taking ability, further diagnostic examination and data interpretation, diagnosis, and professionalism. Conclusion: There are differences in OSCE scores among final-year preclinical students before and during the COVID-19 pandemic. Among the seven competency areas, online learning and assessment can be applied to skills related to history-taking, communication, non-pharmacological management, while other areas require direct hands-on experience.